Effect of potato glycoside alkaloids on mitochondria energy metabolism of Fusarium solani, the root rot pathogen of Lycium barbarum - Li, Ruiyun; Wang, Bin; Chen, Wei; Zhang, Chongqing; Li, Nan; Wang, Yupeng; Yan, Yuke; Sun, Yuyan; He, Jing (Frontiers in Microbiology, 2025)
Fusarium solani is a widely distributed pathogenic fungus that can cause soil borne diseases in various plants and is also one of the main pathogenic bacteria of Lycium barbarum root rot. This study employed tandem mass labeling (TMT) quantitative proteomics technology to investigate the antifungal mechanism of potato glycoside alkaloids (PGA) against Fusarium solani. We elucidated the antifungal mechanism of PGA from the perspective of mitochondrial proteome molecular biology. Furthermore, we identified and annotated the differentially expressed proteins (DEP) of F. solani under PGA stress. A total of 2,412 DEPs were identified, among which 1,083 were significantly up-regulated and 1,329 significantly down-regulated. Subsequent analysis focused on five DEPs related to energy metabolism for verification at both protein and gene levels. Gene Ontology (GO) function analysis revealed that the DEPs were primarily involved in the integral component of the membrane, intrinsic component of the membrane, pyridine-containing compound metabolic processes, carbon-oxygen lyase activity, and the endoplasmic reticulum, with a notable enrichment in membrane components. Furthermore, a total of 195 pathways were identified through KEGG analysis, with significant enrichment in critical pathways including pentose and glucuronate interconversions, propanoate metabolism, various types of N-glycan biosynthesis, the pentose phosphate pathway, and carbon fixation in photosynthetic organisms. The results from both parallel reaction monitoring (PRM) and real-time RT-qPCR were consistent with the overall trends observed in TMT proteomics, thereby confirming the validity of the TMT proteomics analysis. These findings indicate that PGA inhibits the growth of F. solani by impacting mitochondrial energy metabolism. This study reveals the antifungal mechanism of PGA from the perspective of energy metabolism, providing a theoretical basis for the development and application of PGA as a biopesticide.